1983
DOI: 10.1021/ic00149a013
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic oxygen exchange between aqueous vanadyl ions and solvent water

Abstract: The 180 isotopic oxygen exchange of the oxo (yl) oxygens of dr-V02+(aq) is too rapid to measure by static methods. Studies using the rapid formation of [V02(C204)2]3", followed by [Co(en)3]3+ precipitation, revealed complete oxygen exchange during the conversions. Studies on the yl-oxygen exchange of c/r-[V02(C204)2]3' found the rate to be less and the rate equation to be rate = fc0[VO2(C2O4)2]3" + fch[H+][V02(C204)2]3", where A:0 = 0.31 ± 0.1 s"1 and *h = (4.7 ± 1) X 103 s"1 M"1 at 0 °C and a pH <6. Above thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…21 Although there are a number of reports on oxygen exchange between a metal-oxo group and water, quantitative kinetics data for such reactions are rare. [22][23][24][25][26][27][28][29] From the few rate constants that have been measured, it is obvious that these values are a function of the metal, its oxidation state, and the ligand environment, which makes a direct comparison to Fe IV aq O 2+ rather difficult to make. The closest example in the literature is the exchange between traces of water in acetonitrile and the iron(IV)-oxo complex of tetramethylcyclam, for which the rate constant of 5.4 ( 0.6 M -1 s -1 was reported.…”
Section: Discussionmentioning
confidence: 99%
“…21 Although there are a number of reports on oxygen exchange between a metal-oxo group and water, quantitative kinetics data for such reactions are rare. [22][23][24][25][26][27][28][29] From the few rate constants that have been measured, it is obvious that these values are a function of the metal, its oxidation state, and the ligand environment, which makes a direct comparison to Fe IV aq O 2+ rather difficult to make. The closest example in the literature is the exchange between traces of water in acetonitrile and the iron(IV)-oxo complex of tetramethylcyclam, for which the rate constant of 5.4 ( 0.6 M -1 s -1 was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible pathway for introducing the axial 17 O ligand is via the reduced Mo(V) form (Figure ). Mo−OH and Mo−OH 2 species exchange rapidly with water, and proton transfer between these groups and an adjacent MoO group has been shown to facilitate exchange of oxo ligands in coordination compounds. However, a resonance Raman study of the molybdenum domain of recombinant human SO that had been redox cycled in H 2 18 O indicated that only one oxo group exchanged with 18 O at pH 8 …”
mentioning
confidence: 99%
“…Mo-OH and Mo-OH 2 species exchange rapidly with water, and proton transfer between these groups and an adjacent ModO group has been shown to facilitate exchange of oxo ligands in coordination compounds. [22][23][24] However, a resonance Raman study of the molybdenum domain of recombinant human SO that had been redox cycled in H 2 18 O indicated that only one oxo group exchanged with 18 O at pH 8. 25 On the other hand, the higher pH (9.7) and different reduction process in our study might facilitate exchange of the axial oxygen of hpH SO during the ∼1 min reaction with sulfite.…”
mentioning
confidence: 99%